Investigating the role of neighborhood youth organizations in preventing adolescent violent offending: evidence from Chicago - Zimmerman, Gregory M. (Journal of quantitative criminology, 2015)
Objectives Neighborhood youth organizations are a salient community-level resource in the lives of children and adolescents, but empirical research on the aggregate-level relationship between neighborhood crime rates and neighborhood organizations is mixed. This study attempts to clarify and extend prior research by examining (1) whether there is a contextual effect of neighborhood youth organizations on individual violent offending, and (2) whether neighborhood youth organizations have conditioning, beneficial effects that extend beyond the youths who participate in these organizations. Methods Data from two components of the Project on Human Development in Chicago Neighborhoods were utilized in this study: the Community Survey and the Longitudinal Cohort Study. A three-level logistic item response model nested 15,242 violent crime item responses within 1,912 subjects from cohorts aged 9, 12, and 15 years; subjects were nested within 79 neighborhoods across the city of Chicago. Results Neighborhood youth organizations did not have a direct, contextual effect on adolescent violent offending. But, the effects of neighborhood youth organizations were heterogeneous in that they reduced the effects of low self-control on violent crime. Moreover, the conditioning role of neighborhood youth organizations operated partly through child-centered informal social control. Conclusions Neighborhood organizations matter in the etiology of youthful offending, but the ways in which these organizations are relevant are nuanced. Research must continue to grapple with the various mechanisms through which neighborhood organizations operate. Illuminating these processes may hold key insights for designing and implementing neighborhood organizations to prevent adolescent violent offending.